1988
DOI: 10.1128/jcm.26.9.1871-1873.1988
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-linked immunosorbent assays for measurement of reovirus immunoglobulin G, A, and M levels in serum

Abstract: Enzyme-linked immunosorbent assays were developed for the quantitation of anti-reovirus immunoglobulin G (IgG), IgA, and IgM in serum. The assays were specific, sensitive, and reproducible and measured antibodies to the reovirus group antigen. They should permit diagnosis of recent reovirus infection and longitudinal study of the development of reovirus group antibodies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Other advantages are its low cost and use of small amounts of serum. Prior studies have shown ELISA to have limited serotype specificity with regard to reovirus: there is significant crossreactivity between all 3 reovirus serotypes [13,14]. This observation suggests that our assay was capable of detecting antibodies against reovirus serotypes other than type 3, although only antibodies directed against type 3 reovirus were specifically measured in the present study.…”
mentioning
confidence: 70%
“…Other advantages are its low cost and use of small amounts of serum. Prior studies have shown ELISA to have limited serotype specificity with regard to reovirus: there is significant crossreactivity between all 3 reovirus serotypes [13,14]. This observation suggests that our assay was capable of detecting antibodies against reovirus serotypes other than type 3, although only antibodies directed against type 3 reovirus were specifically measured in the present study.…”
mentioning
confidence: 70%